1986
DOI: 10.1016/0741-5214(86)90223-5
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity amputation: The control series

Abstract: Although various techniques to determine amputation level have become available, obvious clinical factors may yet identify patients in whom a major amputation is unlikely to heal. We have analyzed the association of multiple clinical factors with the morbidity of 1028 consecutive amputations performed in 786 patients during a 13-year period. The overall operative mortality rate was 7% (57 of 786 patients). Cardiac complications were the leading cause of death (43%). In the 729 patients surviving operation, 345… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
2
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 18 publications
2
15
2
1
Order By: Relevance
“…We report a rate of wound revision and conversion that is lower than the rates reported in larger series where wound revision ranged between 13.2% and 15.4% and conversion ranged between 9% and 20%. [162728] Also, we did not find a higher rate of local wound complications in the BKA group compared to the AKA group, which is different from previous reports. [2229] The lower rate of local wound complications could be explained by the relatively high rate of staged procedures in our series (40%), since 46% of the procedures were performed in the setting of limb-threatening wet gangrene; two-stage amputation has fewer wound complications than one-stage amputation performed for wet gangrene.…”
Section: Discussioncontrasting
confidence: 99%
“…We report a rate of wound revision and conversion that is lower than the rates reported in larger series where wound revision ranged between 13.2% and 15.4% and conversion ranged between 9% and 20%. [162728] Also, we did not find a higher rate of local wound complications in the BKA group compared to the AKA group, which is different from previous reports. [2229] The lower rate of local wound complications could be explained by the relatively high rate of staged procedures in our series (40%), since 46% of the procedures were performed in the setting of limb-threatening wet gangrene; two-stage amputation has fewer wound complications than one-stage amputation performed for wet gangrene.…”
Section: Discussioncontrasting
confidence: 99%
“…A similar rationale is used to justify performing BKA in patients who are candidates for rehabilitation despite a 20% incidence of wound complications reported for BKA. 28 We have not encountered late wound complications. The shape of the stump distributes the weight over the entire surface of the stump rather than over the condyles as with the standard TKAmp prosthesis.…”
Section: Discussionmentioning
confidence: 95%
“…As people live longer, the complications of diabetes, peripheral vascular disease, and other chronic diseases progressively increase the frequency of lower limb loss. Since these disease states are systemic, previous studies (Bodily and Burgess 1983;Ebskov and Josephsen 1980;Keragy et al 1986) have shown that approximately 33 -50% of surviving patients can be expected to lose their second limb within the 2 -3 years following the first amputation. The number of bilateral lower limb amputees has also increased as a result of trauma and congenital limb deficiencies (Bowker and Michael 1992).…”
Section: Introductionmentioning
confidence: 99%